Alterations of brain network topology and structural-functional connectivity coupling in noise-induced hearing loss based on macroscopic scale - Wang, Aijie; Bao, Xianghua; Wang, Chunye; Huang, Ranran; Wang, Liping; Lv, Minghui; Zhang, Guowei (Frontiers in Neuroscience, 2026)
ObjectiveTo investigate the changes in the global attributes of structural connectivity (SC) and functional connectivity (FC) graph theory, as well as the coupling topological structure of the whole brain SC-FC in patients with noise-induced hearing loss (NIHL).Methods57 NIHL patients and 55 health controls (HCs) were included; resting-state functional magnetic resonance imaging, diffusion tensor imaging, clinical data (scales, laboratory indicators) were collected. The graph theory network analysis of SC and FC, the whole-brain SC-FC coupling were performed, and a correlation analysis was employed to analyze the results in relation to the clinical data.ResultsFor FC, there was no significant difference in the global indices directly between groups (P > 0.05, FDR corrected). For SC, the normalized clustering coefficient (γ) and small-worldness (σ) of the NIHL were higher than those of the HCs (P < 0.05, FDR corrected). There was no significant difference in the SC-FC coupling strength of whole brain between two groups (P > 0.05). The graph attribute indices and coupling values of NIHL were correlated to varying degrees with the results of anxiety scale, coagulation, inflammation and biochemical indices (P < 0.05).ConclusionThe brain network topology structure of NIHL patients is abnormal, but the SC-FC coupling strength does not change significantly. This may provide a basis for understanding the theoretical mechanism of brain neural function remodeling and for future more detailed and diverse studies.